Reconception of Zakat Institutional Management Regulations in Bone District - Tri Suhendra Arbani; Rahmatia HL (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This study aims to unravel the reconceptualization of zakat management arrangements in Bone Regency and the role of local governments and Bazasnas in Zakat Management Arrangements. And to analyze philosophical, sociological, and juridical considerations or foundations for forming Draft Laws or Draft Regional Regulations. This research is legal (legal research). The analysis of this study uses the type of qualitative research. The type of research used is the type of prescriptive analysis research. This regional regulation regarding zakat management in Bone Regency is essential because it has great potential to channel it as a form of poverty alleviation and provide social justice for people who need it. The role of local government of Bone Regency can take several actions, namely: the Role of Zakat Institutions, the Role in Regional Regulations, and the Role in Collecting Community Data on Zakat Assistance Recipients. This regional regulation on zakat management must be re-regulated in updating existing regional regulations. Regional regulations for zakat management are beneficial with the aim of being a regulatory material for good zakat management to increase efficiency and effectiveness. Zakat must be managed institutionally by Islamic Law.